Simulação de Monte Carlo : dosimetria OSL em filmes de Al2O3:C - Souza, Jonathan Silva (2018)
In this work, the Monte Carlo Code (MC) Particle and Heavy Ion Transport code System (PHITS) was applied in the geometric optimization of films 6LiF loaded with Al2O3:C, Optically Stimulated Luminescence (OSL) emitting particles, aiming to predict the dose response in two-dimensional dosimeters. The goal was to optimize the design of this new type of dosimetric film using only computational calculations. During the simulations the films were irradiated with a 60Co source, which emits monoenergetic photons with energy of 1.2 MeV under non-equilibrium conditions on the surface of a water phantom. The MC PHITS code was used to model the geometry of particle dispersion and to investigate the structure of tracks and the energy distribution due to the transportation of secondary particles produced by photon interactions through the films. The simulations were performed varying the diameter of the OSL emitters. The energy deposited by fluence of incident particles did not change with the diameter of the spherical grains that were simulated from 20 mm to 100 mm, resulting in Edep,cor,y/?y=7,38.10-4 MeV cm2, with statistical uncertainty better than 7%. Thus, it has been observed that there is no sensitivity dependence of the film with the size of the Al2O3:C grain constructed for dosimetry photons from a 60Co source. The results indicate that we can obtain films with the use of luminescent materials that are tissue-equivalent (TE) in any matrix, because it is possible to use high fill fractions in the voxel with the OSL material without a great change in energy deposition. Better still, the data also demonstrated that there is a good possibility of making a film considered TE, even using a non-TE OSL material embedded in a TE polymer, which would still provide the possibility of the film being extremely flexible.